2023
DOI: 10.3762/bjoc.19.79
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dark states on the intersystem crossing and thermally activated delayed fluorescence of naphthalimide-phenothiazine dyads

Abstract: A series of 1,8-naphthalimide (NI)-phenothiazine (PTZ) electron donor–acceptor dyads were prepared to study the thermally activated delayed fluorescence (TADF) properties of the dyads, from a point of view of detection of the various transient species. The photophysical properties of the dyads were tuned by changing the electron-donating and the electron-withdrawing capability of the PTZ and NI moieties, respectively, by oxidation of the PTZ unit, or by using different aryl substituents attached to the NI unit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The major part of the CS state decays within 7 ± 1 ps/130 ± 60 ps (biexponential decay), but a small portion of residual signal is persistent in the fs-TA spectra (the lifetime was not determined with ns-TA spectra) . Our results present the rare experimental evidence for the spin-vibronic coupling mechanism of TADF. , …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The major part of the CS state decays within 7 ± 1 ps/130 ± 60 ps (biexponential decay), but a small portion of residual signal is persistent in the fs-TA spectra (the lifetime was not determined with ns-TA spectra) . Our results present the rare experimental evidence for the spin-vibronic coupling mechanism of TADF. , …”
Section: Resultsmentioning
confidence: 59%
“…91 Our results present the rare experimental evidence for the spin-vibronic coupling mechanism of TADF. 98,99 Upon oxidation of the PTZ unit in NDI-Ph-PTZ, the triad NDI-Ph-PTZ-O shows a similar transient absorption character (Figure 8). A broader positive absorption band in the range of 400−700 nm was observed (Figure 8a).…”
Section: Redox Properties and Uv−vis Absorption Of The Radical Anion ...mentioning
confidence: 95%
“…NIS showed an absorption band centered at 438 nm, which is redshifted by 110 nm compared to that of the native NI chromophore. 65–67 In the case of NIS-NH 2 , a further red shift to 526 nm was observed, which is due to the attachment of the amino group at the 4-position of the NI moiety. 51 Interestingly, Rho-NIS showed a major absorption band centered at 453 nm, which is very close to that of NIS .…”
Section: Resultsmentioning
confidence: 96%
“…Recently, this method was used by us to prepare NI-PTZ dyads. 50 The photophysical properties of the dyads were studied by steady-state and time-resolved transient absorption spectroscopic methods.…”
Section: Design and Synthesis Of The Compoundsmentioning
confidence: 99%
“…44 This method has rarely been used in the study of electron donor-acceptor dyad-based TADF emitters. 44,50 Their photophysical properties were studied by UV-vis absorption, fluorescence spectroscopy, femtosecond and nanosecond transient absorption spectroscopy. Our study confirmed that the existence of an admixture of the 3 LE and CT states is critical for TADF and demonstrated that the spin-vibronic coupling of the 3 LE/CT states is essential for TADF.…”
Section: Introductionmentioning
confidence: 99%